Group decision and negotiation - behavior, models, snd support : 19th International Conference, GDN 2019, Loughborough, UK, June 11-15, 2019, Proceedings /: 19th International Conference, GDN 2019, Loughborough, UK, June 11-15, 2019, Proceedings. ([2019]) - Unknown
No abstract available